Association between metabolic syndrome and progression in Parkinson's disease - Saloni Sharma; David Oakes; Shirley Eberly; Carlos Singer; Lowell Jillian; Tanya Simuni (Clinical Epidemiology and Global Health, 2023)
Background: Parkinson's disease (PD) and metabolic syndrome are separate entities that share common underlying pathophysiology. Management strategy for metabolic syndrome is clinically better characterized and finding a positive clinical correlation between the two could lead to a better understanding of Parkinson's disease progression and prognosis. Purpose: To explore the relationship between progression in PD and metabolic syndrome to characterize the underlying pathophysiology, which could then impact the clinical management of PD. Methods: Using modified NCEP (National Cholesterol Education Program) ATP III (Adult Treatment Plan) criteria, patients enrolled in STEADY-PD III (Safety, Tolerability, and Efficacy Assessment of Isradipine) were classified into one of three categories of metabolic syndrome and compared on PD progression over a period of 3 years. Results: Participants with metabolic syndrome showed a trend for more progression in terms of PD, as measured by the total Unified Parkinson's Disease Rating Scale (UPDRS), the motor EDL (Experiences of daily living) scores of the Movement Disorder Society - Unified Parkinson's Disease Rating Scale (MDS-UPDRS), and the Montreal Cognitive Assessment (MoCA). A significant trend for decline in MoCA was found in the group with metabolic syndrome (−0.78), compared with those without metabolic syndrome (0.14). Greater decline in MoCA signifies worse outcomes. Conclusion: The results demonstrate a trend in more clinical progression in PD in subjects with metabolic syndrome. However, results are limited by the sample size and the limited laboratory measurements available. We hope this study will encourage larger sample studies to explore this relationship further.